1970
DOI: 10.1111/j.1476-5381.1970.tb10653.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigations into the mechanism of the antifertility action of minimal doses of megestrol acetate in the rabbit

Abstract: Summary . Experiments have been performed to investigate the mechanism by which low doses of megestrol acetate have an antifertility action. . It was found that the dose of megestrol acetate required to prevent pregnancy in nine of ten New Zealand White rabbits when given on 3 consecutive days, the last of which was the day of insemination, was 50 μg/kg daily. . This treatment reduced the numbers of sperm recoverable from the uterus at various times after insemination, but egg transfer experiments showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1975
1975
1983
1983

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…This work, reviewed by Chang (1976), indicates that progestagens given after ovulation do not produce marked or consistent changes in the rate of egg transport but when given before ovulation cause acceleration and premature entry of embryos into the uterus. Preovulatory progesterone might be active by virtue of its metabolic conversion to oestrogen, but Kendle & Telford (1970) showed similar acceleration following administration of megestrol acetate, a progestagen which does not have oestrogenic activity and is not easily aromatized metabolically (David, Edwards, Fellows & Plummer, 1963). Accele¬ ration of egg transport was also observed in these experiments when administration of megestrol acetate was continued up to the day of autopsy (Day 1, 2 or 3 of pregnancy), indicating that the effect was due to progestagen administration and not to progestagen withdrawal.…”
Section: Introductionmentioning
confidence: 99%
“…This work, reviewed by Chang (1976), indicates that progestagens given after ovulation do not produce marked or consistent changes in the rate of egg transport but when given before ovulation cause acceleration and premature entry of embryos into the uterus. Preovulatory progesterone might be active by virtue of its metabolic conversion to oestrogen, but Kendle & Telford (1970) showed similar acceleration following administration of megestrol acetate, a progestagen which does not have oestrogenic activity and is not easily aromatized metabolically (David, Edwards, Fellows & Plummer, 1963). Accele¬ ration of egg transport was also observed in these experiments when administration of megestrol acetate was continued up to the day of autopsy (Day 1, 2 or 3 of pregnancy), indicating that the effect was due to progestagen administration and not to progestagen withdrawal.…”
Section: Introductionmentioning
confidence: 99%
“…The dose required, however, is very much greater than that required to produce vaginal cornification (see Bennett, Kendle, Vallance & Vickery, 1966). Evidence in the rabbit (Chang, 1966;Kendle & Telford, 1970) indicates the importance of progesterone in the control of egg transport. It is therefore probable that the pharmacological effects of oestrogen are a reflection of their weak antiprogestational activity.…”
Section: Discussionmentioning
confidence: 99%
“…Continuous administration of low doses of progestins offer the closest approach at present, but the problems of compara¬ tively low efficacy and incidence of endometrial side-effects persist (see Mears, Vessey, Andolsek & Oven, 1969;Board, 1971). Animal studies have indicated that this regimen probably advances the changes characteristic of early preg¬ nancy in the maternal reproductive tract, causing asynchrony between the development of the ovum and that of its environment (Kendle & Telford, 1970). This method appears to cause only minimal alterations of physiological processes and it is unlikely that any regimen based on daily administration of drugs can produce greater freedom from side-effects while achieving absolute efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Progesterone or synthetic progestogens given for 3 days prior to ovulation consistently in duce accelerated transport [14,29,[42][43][44]. Eggs can be recovered from the uterus 12 h after ovulation in rabbits treated with 2.5 mg progesterone 48 and 24 h prior to HCG and at the time of HCG [42], When the same dose of progesterone is given with HCG and every 24 h thereafter, a mar ginal delay in transport is observed [42].…”
Section: Physiologic Regulation Of Transportmentioning
confidence: 99%